2003
DOI: 10.1074/jbc.m308089200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of the Acyl Chain Determine Self-phospholipid Antigen Recognition by a CD1d-restricted Invariant NKT (iNKT) Cell

Abstract: Little is known about the antigen specificity of CD1d-restricted T cells, except that they frequently recognize CD1d-expressing antigen-presenting cells in the absence of exogenous antigen. We previously demonstrated that the 24.8.A iNKT cell hybridoma was broadly reactive with CD1d-transfected cell lines and recognized the polar lipid fraction of a tumor cell extract. In the present study, the antigen recognized by the 24.8.A iNKT cell hybridoma was purified to homogeneity and identified as palmitoyl-oleoyl-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
124
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 42 publications
5
124
0
Order By: Relevance
“…a-glucuronosylceramide from Sphingomonas sp. [26][27][28][29] and Ehrlichia sp.[28], a-galactosyldiacylglycerol from Borrelia sp.[30], phosphatidylinositol mannoside from Mycobacterium sp.[31] and phosphoethanolamine [32] have recently been identified as ligands for iNKT cells, although all of these activate iNKT cells to a lesser degree than a-GalCer. Although lysosomal glycosphingolipid, isoglobotrihexosylceramide has been reported as a possible endogenous ligand for iNKT cells [28,33], a recent study argues against this possibility [34].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…a-glucuronosylceramide from Sphingomonas sp. [26][27][28][29] and Ehrlichia sp.[28], a-galactosyldiacylglycerol from Borrelia sp.[30], phosphatidylinositol mannoside from Mycobacterium sp.[31] and phosphoethanolamine [32] have recently been identified as ligands for iNKT cells, although all of these activate iNKT cells to a lesser degree than a-GalCer. Although lysosomal glycosphingolipid, isoglobotrihexosylceramide has been reported as a possible endogenous ligand for iNKT cells [28,33], a recent study argues against this possibility [34].…”
mentioning
confidence: 99%
“…[31] and phosphoethanolamine [32] have recently been identified as ligands for iNKT cells, although all of these activate iNKT cells to a lesser degree than a-GalCer. Although lysosomal glycosphingolipid, isoglobotrihexosylceramide has been reported as a possible endogenous ligand for iNKT cells [28,33], a recent study argues against this possibility [34].…”
mentioning
confidence: 99%
“…These chemical groups have a major effect on the shape of lipids, which is commonly underappreciated. Acyl chain unsaturations (alkene groups) generate a kink and limit flexibility in the acyl chain structure (30). Thus, alkene groups or other acyl-chain modifications may cause lipids to adopt a shape that is not compatible with the dimensions of the SapB hydrophobic pocket or may prevent acyl chains from adoptively fitting into the hydrophobic pocket by restricting its chain.…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, the gross geometric differences between isomeric lipids with cis and trans double bonds have a significant impact on molecular structure and, thus, their biophysical and biochemical properties. For example, Rauch et al showed that the configuration of the double bond in PE 16:0/18:1 was a critical determinant of its recognition as a protein-presented antigen for T cells [37]. Despite its recognized importance, the ability to rapidly establish double bond stereochemistry in complex lipids presents a significant analytical challenge.…”
Section: Double Bond Stereochemistrymentioning
confidence: 99%